High-Temperature Performance of Asphalt Mixtures: Preliminary Analysis for the Standard Technical Index Based on Gray Relational Analysis Method - Jian Xu; Yan Gong; Li-Biao Chen; Tao Ma; Jun-Cheng Zeng; Er-Hu Yan; Guang-Shu Xiao (Advances in Materials Science and Engineering)
Aiming to evaluate the high-temperature performance of asphalt binders and asphalt mixtures and to investigate the reliability of the standard technical indexes to evaluate the performance of the asphalt, six typically used asphalt types were employed in this study. The standard high-temperature rheological test, the multiple stress creep recovery (MSCR) test, and the zero-shear viscosity (ZSV) test were employed to characterize the high-temperature performance and non-Newtonian fluid properties of the asphalt. Meanwhile, the high-temperature performance of the asphalt mixture was evaluated through the rutting tests based on the mixture design of AC-13. In general, the modified asphalt performed better than the unmodified asphalt according to the high-temperature rheological properties tests. The ranking of the six kinds of asphalt was confirmed to be different in various laboratory tests. The test results of the asphalt binders showed that the Tafpack Super- (TPS-) modified asphalt performed best in the MSCR and ZSV tests, while the low-grade asphalt PEN20 had the best technical indexes in the dynamic shear rheometer (DSR) test. Besides, the relation between the asphalt and the asphalt mixture was analyzed by gray relational analysis (GRA) method. The present rutting indicator G∗/sin δ and G∗/1−sin δ⋅ tan δ−1 for evaluating the asphalt mixtures’ high-temperature performance might no longer be suitable. The Cross/Williamson model was the most suitable for calculating and fitting the ZSV, which could be used as the key indicator of the high-temperature performance evaluation of the asphalt. This work lays a foundation for the further study of the high-temperature performance evaluation of asphalt binders.